Which line contains the fallacy in this mathematical proof?
1. Let a and b be equal non-zero quantities.
a = b
2. Multiply both sides by a.
a2 = ab
3. Subtract b2.
a2 - b2 = ab - b2
4. Factor both sides.
(a - b)(a + b) = b(a - b)
5. Divide out (a - b).
(a + b) = b
6. Substitute a = b.
b + b = b
7. Simplify.
2b = b
8. Divide by b.
2 = 1
Warning!!! Answer:
1. Let a and b be equal non-zero quantities.
a = b
2. Multiply both sides by a.
a2 = ab
3. Subtract b2.
a2 - b2 = ab - b2
4. Factor both sides.
(a - b)(a + b) = b(a - b)
5. Divide out (a - b).
(a + b) = b
6. Substitute a = b.
b + b = b
7. Simplify.
2b = b
8. Divide by b.
2 = 1
Warning!!! Answer: